(untitled) (Research, Society and Development, 2022)
Diseases as a group of diseases that manifest diverse and sometimes devastating diseases for the patient. These are low-incidence but high-morbidity diseases. The primary and fundamental manifestation consists of vesicles and bullae. This aimed to study the literature on issues highlighted in the oral mucosa, studying its clinical presentation, diagnosis, as well as the importance of a clinical treatment in its clinical presentation. For the construction of this work, a bibliographic survey was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect databases, using the Mendeley reference manager. Scientific studies report that there are several facilities and vesicles that affect the oral literature. These diseases involve herpes simplex, varicella zoster, and pemphigus. Illnesses can impair the quality of the patient who complains of life problems with injuries. Therefore, it becomes indispensable that early or early health professionals can, from time to time, that as resources serve as fundamental indicators in the diagnosis of the disease.